2021
DOI: 10.1557/s43578-021-00422-z
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of TiB2-reinforced Ti–35Nb–7Zr–5Ta processed by laser-powder bed fusion

Abstract: The Ti–35Nb–7Zr–5Ta (wt%, TNZT) alloy was reinforced with TiB2 and synthesized by L-PBF. The relatively small TiB2 particles change the solidification structure from cellular to columnar-dendritic and lead to submicron TiB precipitation in the β matrix. This results in pronounced grain refinement and reduction of texture. However, the microstructure of the additively manufactured TNZT-TiB2 is still different from the as-cast, unreinforced TNZT, which contains equiaxed and randomly oriented grains. The β phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
4
0
4
Order By: Relevance
“…The bulk samples produced by unidirectional-Y, R79, and CHB scanning strategies show a β single-phase structure. The high concentration of β stabilizing elements in the TNZT alloy combined with the high cooling rates of the L-PBF process is sufficient to inhibit the precipitation of other phases [20]. Therefore, although the scanning strategy is expected to influence the heat distribution between adjacent layers, it does not affect the phase formation of the TNZT alloy.…”
Section: Microstructure Of the L-pbf As-built Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The bulk samples produced by unidirectional-Y, R79, and CHB scanning strategies show a β single-phase structure. The high concentration of β stabilizing elements in the TNZT alloy combined with the high cooling rates of the L-PBF process is sufficient to inhibit the precipitation of other phases [20]. Therefore, although the scanning strategy is expected to influence the heat distribution between adjacent layers, it does not affect the phase formation of the TNZT alloy.…”
Section: Microstructure Of the L-pbf As-built Samplesmentioning
confidence: 99%
“…The formation of a cellular structure independently of the scanning strategy with a high degree of cell refinement is visible in samples produced with the three scanning strategies (cell thickness of approximately 600 nm). Several studies also showed the formation of similar microstructures for β-Ti alloys [20,[24][25][26][27].…”
Section: Microstructure Of the L-pbf As-built Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Para superar essas desvantagens biológicas e mecânicas, ligas de beta titânio (β-Ti) são desenvolvidas por apresentarem alta resistência específica, menor módulo de elasticidade, resistência à corrosão e elementos não tóxicos como tântalo (Ta), zircônio (Zr), molibdênio (Mo), e estanho (Sn) quando comparadas a Ti-6Al-4V, mais utilizada (BATALHA et al, 2022;CAMPANELLI et al, 2018;PÉREZ et al, 2020;BOLFARINI, 2019. ABDEL-HADY GEPREEL; NIINOMI, 2013 em seu artigo de opinião inferiram que as ligas de beta titânio são promissoras para implantes de alta duração por apresentarem alta compatibilidade mecânica, ou seja, alta resistência ao desgaste e baixo módulo de elasticidade, e ser composta por elementos biocompatíveis como nióbio (Nb), Ta, Zr, Mo, Sn etc, mas ressaltaram a necessidade da maior concentração na liga ser por elementos de baixo custo como ferro (Fe), manganês (Mn), Sn, e silício (Si).…”
Section: Introductionunclassified
“…do Ti e sua solubilidade nas fases α e β (PLAINE; DA SILVA; BOLFARINI, 2019). Dentre elas, a liga Ti-35Nb-7Zr-5Ta (TNZT) é considerada beta por ser composta de Nb e Ta considerados estabilizadores da fase β e Zr elemento neutro que se comporta como estabilizador de fase β quando em contato com elementos estabilizadores β, e promissora por combinar baixo módulo de elasticidade (50-70GPa), alta resistência, e biocompatibilidade (BATALHA et al, 2020a(BATALHA et al, , 2020b(BATALHA et al, , 2022.…”
Section: Introductionunclassified